Inclusive Islamic Morality in Indonesia: An Analysis from the Perspective of Nurcholish Madjid - Amiruddin, Amiruddin; Asir , Asir; Abdillah, Achmad (At-Tafkir, 2025)
This study is motivated by the persistence of exclusivism, intolerance, and social fragmentation among religious communities in Indonesia, which reflects a significant gap between the inclusive moral principles of Islam and the socio-religious realities in society. The research aims to analyze the concept of inclusive Islamic morality from the perspective of Nurcholish Madjid and to explore its relevance in addressing contemporary challenges related to pluralism, religious harmony, and democratic citizenship. Employing a qualitative approach through library research, this study examines Madjid’s major works on pluralism, secularization, Islamic reform, and the relationship between religion and the state. The findings reveal that Madjid’s conception of inclusive Islamic morality is grounded in the principles of liberating monotheism, religious inclusivity, rationality, and openness to modernity. He emphasizes the purification of Islam from political instrumentalization and symbolic formalism so that Islamic ethics may function as universal public values. The results indicate that Madjid’s ideas offer substantial conceptual resources for countering intolerance, identity-based radicalism, and sectarian politics in contemporary Indonesia. The study concludes that integrating these principles into religious education, public discourse, and socio-religious policy is essential for strengthening a culture of dialogue, respect for diversity, and democratic citizenship.